Systematic Review of Current Trends in Precision Agricultural Model to Address Food Insecurity Challenges - S. A. Alamu (Journal of Applied Sciences and Environmental Management)
Agriculture contributes significantly to socio-economic development, food security, and employment opportunities for a large number of people globally. Hence, the objective of this paper was to explore a systematic review of current trends in precision agricultural model to address food insecurity challenges using appropriate standard techniques. The results revealed the potential of precision agriculture in solving food insecurity challenges, minimizing agricultural input wastage, and promoting lucrative farming. This agricultural model builds on innovative technology collect data, analyze, and make critical predictions thereby providing lasting solutions to complex agricultural challenges. According to the United Nations, about 2/3rd of the world's population will be living in urban areas by 2050. This report indicated the need to incorporate emerging technological innovation into agriculture to increase food production and ensure food availability. Robotics and drones are innovative technologies with the potential to change the agricultural landscape, especially in developing nations. Consequently, the application of automaton, AI, and predictive tools to tackle real-time agricultural challenges is at the nascent stage in the developing areas of the world. Financial constraints, lack of technical knowledge, and lack of government support remains major challenges influencing precision agriculture in developing countries. Finally, adopting a precision agricultural model by farmers will help in pest detection, and predicting crops with favourable output, to cope with the current food insecurity challenges, especially in developing countries.